ОЦІНКА ЕКОЛОГІЧНОГО СТАНУ СЕВАСТОПОЛЬСЬКИХ БУХТ ЗА ОСНОВНИМИ ХІМІЧНИМИ І МІКРОБІОЛОГІЧНИМИ КРИТЕРІЯМИ - Рубцова, С. І.; Тіхонова, О. А.; Бурдіян, Н. В.; Дорошенко, Ю. В. (Marine Ecological Journal, 2023)
The ecological state of the Sevastopol bays is considered on the basis of sanitary-biological survey of 2009 and long-term information of department of marine sanitary hydrobiology of IBSS NASU, co-operating of marine organisms and their associations is studied with contamination, done suggestion on the improvement of the ecological state of equatorials, classification of the Sevastopol bays is made on the degree of ecological situation. The criteria of estimation of the ecological state of marine waterside areas are analyzed on basic chemical and microbiological indexes. One way to improve of the ecological state of equatorials based on creation of the artificial hydrobiological systems for cleaning salt waters.